PENGARUH STORE ATMOSPHERE TERHADAP KEPUTUSAN PEMBELIAN PADA WAROENG BOEDJANG CAFE KARAWANG - Tamsir, Sonya Pebriani; Hamid, Satim; Sodiq, Jafar (Lembaga Penelitian dan Pendidikan Mandala, 2022)
This study aims to determine how the influence of store atmosphere on purchasing decisions at Waroeng Boedjang Cafe in Karawang. The sample of this study was 50 customers using non-probability sampling technique. Questionnaires are used to obtain respondents' answers about the variable X Store Atmosphere and variable Y Purchase Decision. Data were analyzed using linear regression analysis with SPSS version 2.5 to answer the research hypothesis. The results of the study found that there was an influence between Store Atmosphere on Purchase Decisions at Waroeng Boedjang Cafe. Then Store Atmosphere has a positive influence with an r value of 0.837 and has a contribution of 70.0% influence on the Purchase Decision of Waroeng Boedjang Cafe. While the remaining 30.0% is influenced by other factors, so it is important for Waroeng Boedjang Cafe to pay attention to the Store Atmosphere to attract more customers and potential customers.